PERAN UMKM MENGHADAPI MEA 2015 MELALUI PELATIHAN BAHASA INGGRIS - Rianto Nurcahyo; Raja Halim Harahap; Didiet Gharnaditya (Jurnal Ilmu Manajemen & Ekonomika, 2015)
Entering the era of globalization, better known as free market requires every individual to prepare reliable resources, especially in the field of Science and Technology. In order to master these demands, it is required adequate knowledge so that they can use it in dealing with the demands of a globalized world full of competition. In this regard, the role of the English language is required both in mastering communication technologies and to interact directly; moreover, the presence of the media especially the Internet will force people to learn English. As a means of global communication, English should be actively mastered both orally and in written. In an increasingly globalized business world, there are more local Indonesian companies entering into the world market, and growing number of international companies.This research is an attempt to create the roles of exporters, especially the Micro, Small and Medium Enterprises (SMEs) through the products produced by the exporters themselves. Of the Indonesian export revenue number to other countries, the value of Indonesia's exports is relatively low, one of the constraints faced by exporters is in terms of the ability of a foreign language, namely English. Mastery of English is the main capital to open international trading communication.This method is expected to eventually be able to provide additional knowledge and self-confidence for the exporters who want to market their products abroad, the title of this study is Preparing SMEs in facing AEC 2015 through English training program to obtain export market (Keywords: Training, Export, ASEAN, MEA)Keywords: Training, Export, ASEAN, MEA